Model Permainan Tradisional terhadap Perilaku Sosial ABK SLB Ceria Mandiri Blora - Aflahudin, Ahmad; Nurharsono, Tri (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to identify and describe traditional games on the social behavior of children with special needs. This type of research is a qualitative research using an ethnographic approach. The subjects in this study were Ceria Mandiri SLB students. Data collection techniques using triangulation techniques, namely observation, interviews and documentation.The results of this study are the social behavior of ABK students in the socialization aspect, namely students can socialize well, are polite in getting along with other students but sometimes are still mischievous and cry when disturbed by their environment. Then on the interaction aspect, ABK students can interact with their friends even though ABK students are often angry when they feel disturbed. Not only that, ABK students look away when students feel awkward. Furthermore, on the role model aspect, that is not causing fights, but if they will react otherwise such as getting angry, hitting when they are not comfortable. Next is the communication aspect, students can establish conducive communication even though the communication process occurs both orally and in sign language.Based on the results of the study, it can be concluded that the learning process at SLB Ceria Mandiri is still not varied. There needs to be a lot of innovation to increase enthusiasm and increase children's creativity to be better in the learning process.